Active Caspases and Cleaved Cytokeratins Are Sequestered into Cytoplasmic Inclusions in Trail-Induced Apoptosis - MacFarlane, Marion (The Rockefeller University Press, 2000)
Tumor necrosis factor–related apoptosis- inducing ligand (TRAIL) –induced apoptosis, in transformed human breast epithelial MCF-7 cells, resulted in a time-dependent activation of the initiator caspases-8 and -9 and the effector caspase-7. Cleavage of caspase-8 and its preferred substrate, Bid, preceded processing of caspases-7 and -9, indicating that caspase-8 is the apical initiator caspase in TRAIL-induced apoptosis. Using transient transfection of COOH-terminal–tagged green fluorescent protein fusion constructs, caspases-3, -7, and -8 were localized throughout the cytoplasm of MCF-7 cells. TRAIL-induced apoptosis resulted in activation of caspases-3 and -7, and the redistribution of most of their detectable catalytically active small subunits into large spheroidal cytoplasmic inclusions, which lacked a limiting membrane. These inclusions, which were also induced in untransfected cells, contained cytokeratins 8, 18, and 19, together with both a phosphorylated form and a caspase-cleavage fragment of cytokeratin 18. Similarly, in untransfected breast HBL100 and lung A549 epithelial cells, TRAIL induced the formation of cytoplasmic inclusions that contained cleaved cytokeratin 18 and colocalized with active endogenous caspase-3. We propose that effector caspase-mediated cleavage of cytokeratins, resulting in disassembly of the cytoskeleton and formation of cytoplasmic inclusions, may be a characteristic feature of epithelial cell apoptosis.